2013
DOI: 10.1097/bpo.0b013e31829494c0
|View full text |Cite
|
Sign up to set email alerts
|

Hyperactivity and the Psychological Burden of Perthes Disease

Abstract: There was a marked psychological burden among individuals with LCPD, which was most marked amongst individuals with a recent diagnosis. The breadth and inferred temporality of these disturbances may be a function of the disease process, through restriction of activities and disability, or may be a fundamental disease characteristic related directly to disease or to its etiological determinant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…Especially in adults, neurobehavioral aspects of ADHD can change from hyperactivity to more inattentiveness or depression (Yang et al 2013), which may explain the higher risk of depression in individuals with LCPD than in their controls, and which also supports our hypothesis (2). While the association of LCPD with “emotional symptoms” (Perry et al 2013) has been described, to our knowledge ours is the first study to investigate associations between LCPD and depression as a formal diagnosis. The higher risk of depression could also be a result of the psychological burden of LCPD as a response to chronic pain, restriction in physical activity, and the relatively uncertain outcome of LCPD compared to other chronic diseases (Cassileth et al 1984, Moussavi et al 2007).…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Especially in adults, neurobehavioral aspects of ADHD can change from hyperactivity to more inattentiveness or depression (Yang et al 2013), which may explain the higher risk of depression in individuals with LCPD than in their controls, and which also supports our hypothesis (2). While the association of LCPD with “emotional symptoms” (Perry et al 2013) has been described, to our knowledge ours is the first study to investigate associations between LCPD and depression as a formal diagnosis. The higher risk of depression could also be a result of the psychological burden of LCPD as a response to chronic pain, restriction in physical activity, and the relatively uncertain outcome of LCPD compared to other chronic diseases (Cassileth et al 1984, Moussavi et al 2007).…”
Section: Discussionmentioning
confidence: 91%
“…In 1993, Loder et al (1993) found in a group of 24 children with LCPD that one-third had abnormally high scores in profiles associated with ADHD. In a case-control study of 619 individuals with LCPD between the ages of 0 and 14 years, Perry et al (2013) found hyperactivity associated with LCPD but could not find a significantly higher risk of diagnosis of ADHD (Perry et al 2012a). Although ADHD is commonly diagnosed between 5 and 8 years of age, a delay between age at onset and age at diagnosis is not unusual.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The study was part of a broader study, some of which has been described previously [21][22] . Cases were drawn from a regional Perthes' register.…”
Section: Methodsmentioning
confidence: 99%
“…A number of studies have shown a strong association with socioeconomic deprivation in childhood. [2][3][4] Other proposed associations include small stature, 5 dietary deficiencies, 6 passive smoking, 7,8 childhood hyperactivity, 9 white European ancestry, latitude distance from the equator, 10 and an inherited predisposition to abnormal clotting. 11,12 In their early descriptions of LCPD, both Jacques Calvé 13 and Georg Perthes 14 described siblings with the disease.…”
Section: Legg-calvé-perthes Disease (Lcpd)mentioning
confidence: 99%